Risiko kepatuhan dalam perbankan syariah: Antara norma hukum dan etika syariah - Syakuro, Muhammad Kifah Abdan (Maliki Interdisciplinary Journal, 2025)
Islamic banking in Indonesia faces unique compliance risks because it must comply with two regulatory systems at once: legal norms and Islamic sharia principles or ethics. The risks that occur not only impact the legal aspects, but can also damage reputation and erode public trust. This article reviews the definition and scope of risks inherent in Islamic banks, as well as the important role of legal norms and sharia ethics in preventing violations. Case studies, such as the case of Bank Mega Syariah, show the real consequences of the failure to manage the risks inherent. The challenge of harmonizing state law and sharia principles is highlighted, especially in the context of dual propaganda and different interpretations of regulations. This article also discusses mitigation strategies that can be implemented in an integrated manner, including enforcement of sharia supervision, internal and external audits, and development of a culture of compliance. With a holistic approach, Islamic banks are expected to be able to understand risks effectively without ignoring the integrity of Islamic values.